2010
DOI: 10.1175/2009waf2222310.1
|View full text |Cite
|
Sign up to set email alerts
|

Household Evacuation Decision Making and the Benefits of Improved Hurricane Forecasting: Developing a Framework for Assessment

Abstract: Hurricane warnings are the primary sources of information that enable the public to assess the risk and develop responses to threats from hurricanes. These warnings have significantly reduced the number of hurricane-related fatalities in the last several decades. Further investment in the science and implementation of the warning system is a primary mission of the National Weather Service and its partners. It is important that the weather community understand the public's preferences and values for such invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 22 publications
4
53
1
Order By: Relevance
“…Some studies found that warning information from authorities had a significant positive impact on household evacuation willingness (Wilmot and Mei 2004;Burnside et al 2007;Lazo et al 2015;Lim et al 2016). Other studies found that warning information from a family member or friend also had a significant impact on household evacuation willingness (Lazo et al 2010;Widesner et al 2013), while some studies did not (Lazo et al 2015). Dash and Gladwin (2007) found that people were more likely to evacuate if they heard the warning in person from a family member, friend, or authority figure, rather than just from the media; thus, social influence was an important variable to predict the evacuation willingness of households.…”
Section: Household Characteristics and Relocation/ Evacuation Willingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that warning information from authorities had a significant positive impact on household evacuation willingness (Wilmot and Mei 2004;Burnside et al 2007;Lazo et al 2015;Lim et al 2016). Other studies found that warning information from a family member or friend also had a significant impact on household evacuation willingness (Lazo et al 2010;Widesner et al 2013), while some studies did not (Lazo et al 2015). Dash and Gladwin (2007) found that people were more likely to evacuate if they heard the warning in person from a family member, friend, or authority figure, rather than just from the media; thus, social influence was an important variable to predict the evacuation willingness of households.…”
Section: Household Characteristics and Relocation/ Evacuation Willingmentioning
confidence: 99%
“…A few studies have shown that individuals with higher educational levels were more likely to relocate/evacuate than others (Hasan et al 2011), as well as revealing other differences in evacuation decision making (Whitehead et al 2000;Stein et al 2013;Lazo et al 2015;Lim et al 2016). Some studies have shown that prior experience in disaster situations was slightly significant in predicting the probability of evacuation (Bateman and Edwards 2002;Burnside et al 2007;Adeola 2008;Lazo et al 2015), while other studies found a negative or no significant relationship between past experience and relocation/evacuation willingness (Lindell et al 2005;Lazo et al 2010). …”
Section: Individual Characteristics and Relocation/ Evacuation Willinmentioning
confidence: 99%
“…Although there is a reasonably large literature describing some of the sociodemographic correlates of hurricane risk perceptions and information utilization, (12)(13)(14)(15)(16)(17)(18)(19) almost all of it draws on field surveys conducted days or weeks after storm events. (20)(21)(22)(23) Because residents' memories are likely to be imperfect, we currently know far less than we would like to about the dynamics of how information search patterns change over time during the course of storm threats, the kinds of information that serve to trigger decisions to take protective action, and how these dynamics vary across individuals.…”
Section: The Dynamics Of Hurricane Risk Responsementioning
confidence: 99%
“…Also 26 secondary indices (including population density, percent of ethnic minorities, percent of illiterate, ratio of unemployment, percent of social welfare, per capita income etc.) were obtained according to the characteristics of Beijing and some relevant studies [5,6,19,20]. Details are shown in Figure 1.…”
Section: Influencing Factors and The Social Vulnerability Index Systemmentioning
confidence: 99%